Reliability of Gallon-Jug Shelf-Transfer Power Equations in Older Women. Issue 5 (13th May 2023) - Ly, Anna; Strand, Keri L.; Courtney, Kylie J.; Barry, Sarah S.; Parrino, Rosalia L.; Liscano, Jose A.; Trebotich, Thomas L.; Martin-Diala, Chimaobim; Martin, Erick; Signorile, Joseph F.
Abstract: Ly, A, Strand, KL, Courtney, KJ, Barry, SS, Liscano, JA, Trebotich, TL, Martin-Diala, C, Martin, E, and Signorile, JF. Reliability of gallon-jug shelf-transfer test power equations in older women. J Strength Cond Res 37(5): 1124–1130, 2023—This study examined the test-retest reliability of the gallon-jug shelf-transfer (GJST) test as a measure of upper-body functional power in older women. Although the validity of the predictive equations for power during the GJST test has been established, for the test to be viable in either a laboratory or clinical environment, between-day and within-day reliability must be established. Thirty-four independently living older women (mean ± SD : 75.0 ± 6.4 years) performed 2 sets of 3 repetitions of the GJST test on 2 days separated by at least 48 hours. Using the established predictive equations, the values for peak power and average power were then computed. Statistical analyses to assess reliability included intraclass correlation coefficient, coefficient of variation (CV), SEM, minimal detectable change (MDC), and Cronbach's α values. Furthermore, Bland-Altman plots evaluated the agreement between the tests. Intraclass correlation coefficient (>0.91, p < 0 001), CV (<8.1%), SEM (<5.94 W), MDC (<14 W), and Cronbach's α (>0.95) indicated excellent reliability. The lines of equality for all Bland-Altman plots fell within the 95% confidence interval of the mean difference, implying that there were no significant differences between tests. Furthermore, bias values were small (<11.15 W), and the limits of agreement (LOA) were within an acceptable range. Based on our statistical analyses, the GJST test is a highly reliable assessment for determining object transfer power for healthy older women.